CZARDAS AND GOULASH – IMAGES OF THE HUNGARIAN “OTHERNESS” IN KRZYSZTOF VARGA’S OUTPUT - Czyżak, Agnieszka (Porównania, 2018)
The article contains interpretations of two compositions written by Krzysztof Varga, Gulasz z turula (2007) and Czardasz z mangalicą (2014). Those works – with their character bordering on autobiography and reportage – constitute a recognition of the contemporary condition of collective consciousness, especially in Hungary, but also in Poland. Imagology as a cultural fact and the methodology of investigating images and ideas assuming the form of myths, patterns or motifs turns out to be a very useful for cultural (postcolonial and comparative) studies.